Case report: Combined therapy of bilateral subthalamic nucleus deep brain stimulation and spinal cord stimulation significantly improves motor function in a patient with multiple system atrophy with predominant parkinsonism - Li, Jiping; Mei, Shanshan; Zhang, Xiaohua; Wang, Yunpeng; Jia, Xiaofei; Liu, Jinlong; Xu, Erhe; Mao, Wei; Zhang, Yuqing (Frontiers in Neuroscience, 2022)
Multiple system atrophy with predominant parkinsonism (MSA-P) is a highly incapacitating disease with a short life-expectancy and symptomatic therapy is still limited. In this report, we present the case of a 65-year-old female with a 3-year history of severe rigidity, bradykinesia, and gait dysfunction alongside severe freezing of gait who diagnosed as MSA-P. She underwent combined therapy of bilateral subthalamic nucleus-deep brain stimulation (STN-DBS) and low-thoracic spinal cord stimulation (SCS). The double-blind evaluation of the Movement Disorder Society Sponsored Revision of the Unified Parkinson’s Disease Rating Scale part III (MDS-UPDRS III) and 7-meter Timed Up and Go (TUG) at follow-ups showed her cardinal parkinsonian symptoms benefit significantly from DBS stimulation, while, the improvement of SCS was mainly embodied in lower limb symptoms. The combined stimulation achieved a better improvement of motor function than either DBS or SCS stimulation alone. Most notably, the improvement of lower limb symptoms was significantly enhanced by the combined stimulation.